Subsurface mesoscale eddies in the east of the Philippines: three-dimensional biogeochemical structures and transports - Ding, Ya-nan; Xu, Anqi; Shi, Suixiang; Liu, Kexiu; Gao, Zhigang; Wu, Xinrong; Nan, Feng; Yu, Fei (Frontiers in Marine Science, 2024)
Subsurface eddies (SSEs) are a particular type of oceanic eddy that is a common feature in the ocean. The biogeochemical properties of the SSEs differ from those of surface eddies (SEs) and surrounding water, due to their unique physical processes. The biogeochemical property of SSEs in the east of the Philippines were investigated using numerical simulations, including their statistical characteristics, three-dimensional biogeochemical structures and transports, as well as contribution to changes in biogeochemical variables. A total of 501 subsurface anticyclonic eddies (SSAE) and 345 subsurface cyclonic eddies (SSCE) were identified during 2019–2022. Compared with the SEs, the temperature, nitrate (NO3) and dissolved oxygen (DO) anomalies of the SSEs east of the Philippines have two significant anomalous cores of opposite phase: at 200–400 m and 600–800 m, respectively, with the location of the largest meridional velocity (~400 m) being the boundary between positive and negative anomalies. SSEs also play an essential role in influencing chlorophyll (CHL) distribution, with SSAE (SSCE) causing an increase (decrease) in CHL at the euphotic zone (~110 m). In addition, the SSEs-induced NO3, DO and CHL transport and their contributions to the changes in biogeochemical variables were also illustrated for the first time. In more than half of the investigated region, there was a net westward transport of DO and a predominant eastward transport of NO3, primarily attributed to SSAE. Regarding CHL transport in the euphotic zone, SSAE is the primary contributor, with a notable westward CHL transport observed in the study area, and mainly a northward transport occurring north of 12°N. In particular, the NO3 concentration in the euphotic zone was considerably increased by SSAE (up to 12.6%) under average conditions, contributing to primary productivity, which can be critical for biological processes.